SPEM: a state-of-the-art instrument for high resolution molecular imaging of small animal organs - Marilia Alves dos Reis; Jorge Mejia; Ilza Rosa Batista; Marycel Rosa Felisa Figols de Barboza; Solange Amorim Nogueira; Jairo Wagner; Francisco Romero Cabral; Petrick Marcellus Victorio Mendonça Davoglio; Vanessa Costhek Abílio; Geng Fu; Nan Li; Ling Jian Meng; et al. (Einstein (São Paulo), 2012)
OBJECTIVE: To describe the Single Photon Emission Microscope (SPEM), a state-of-the-art instrument for small animal SPECT imaging, and characterize its performance presenting typical images of different animal organs. METHODS: SPEM consists of two independent imaging devices based on high resolution scintillators, high sensitivity and resolution Electron-Multiplying CCDs and multi-pinhole collimators. During image acquisition, the mouse is placed in a rotational vertical holder between the imaging devices. Subsequently, an appropriate software tool based on the Maximum Likelihood algorithm iteratively produces the volumetric image. Radiopharmaceuticals for imaging kidneys, heart, thyroid and brain were used. The mice were injected with 74 to 148 MBq/0,3mL and scanned for 40 to 80 minutes, 30 to 60 minutes afterwards. During this procedure, the animals remained under ketamine/xilazine anesthesia. RESULTS: SPEM images of different mouse organs are presented, attesting the imaging capabilities of the instrument. CONCLUSION: SPEM is an innovative technology for small animal SPECT imaging providing high resolution images with appropriate sensitivity for pre-clinical research. Its use with appropriate radiotracers will allow translational investigation of several animal models of human diseases, their pharmacological treatment and the development of potential new therapeutic agents.